MARKET PARTICIPATION OF SMALLHOLDER MAIZE FARMERS: A STUDY OF INFLUENTIAL FACTORS IN BENUE STATE, NIGERIA - Adakole, Benjamin Terlumun (Research Journal of Economics and Sustainable Development, 2024)
Considering the smallholder farmers’ market participation is a crucial issue in improving household welfare in rural areas and poverty reduction in developing countries like Nigeria. Maize production has not been given due attention; which has potential production volume and market ability. Therefore, this study was designed to identify determinants of market participation among smallholder maize farmers in Benue State, Nigeria. Data for this study were collected through questionnaire administered to maize farmers. Both purposive and random sampling techniques were used to draw an appropriate sample of 320 maize producer households for the study. The data were analysed using descriptive statistics and binary logistic regression model. The result revealed that The Cox&Snell (R Square) was 0.68 signifying that sex, age, marital status, household size, education, farming experience, farm size, output and market information accounted for 68 percent factors influencing market participation by maize farmers in Benue State, Nigeria. The Result furthermore revealed that education, farm size and output were the major determinants of market participation by maize farmers in Benue State. The constraints to market participation faced by smallholder farmers in Benue State included bad roads (92.2%), Cost of transportation (82.2%) and High taxes (79.1%). The findings of this research indicates that higher levels of maize production enhance small holders’ participation in market. It is recommended that strategies that aim at improving households’ capacity to produce Surplus production like optimal allocation of resources such as land, machinery and credit will enhance productivity and promote smallholders market participation